The critical success factors of bumiputera entrepreneurs in franchise industry / Shaira Ismail and Nor Azizah Mohammad Amin (Institute of Research, Development and Commercialization, 2005)
The paper presents statistical and empirical study on the business Critical Success Factors (CSFs) or in other words "the sustainable competitive advantage" which lead to the successfully of managing franchise business. The study is specifically focus on the Malaysian franchising industry. The main intention of the study is to analyze, examine and compare the two focused groups, Bumiputera and Non Bumiputera franchised enterprises on their comparative advantage to explore their differences or similarities on business approaches and perceptions in relations to the business competitive advantage. This study is focused on Malaysian entrepreneurs; Bumiputera and Non Bumiputera franchisees in the franchising industry. The research covers respondents in Negeri Sembilan and Pulau Pinang. The objectives of the study are; 1. to identify the Critical Success Factors (CSFs) that are essential for successful doing business among the Bumiputera and Non Bumiputera franchisees; 2. to examine the types of support, assistance and guidance offered and provided by the franchisor to their franchisees in managing the business successfully; 3. to examine the degree of "relationships" between the franchisor and franchisee and 4. to identify the differences and similarities between Bumiputera and Non Bumiputera on business approaches and their perceptions towards the business competitive advantage Research methodology is done to obtain the primary data through questionnaires and personal interviewing with the franchisees. We have distributed 50 questionnaires and 68% of the questionnaires were completed and returned back to us.